High microwave dielectric performance and applications in antenna of novel Li7La3Zr2O12 ceramics - He, Guo Qiang; Du, Chao; Wang, Zhen Tao; Bao, Jian; Fang, Zhen; Wang, Chang Hao; Xi, Zhao Chen; Darwish, Moustafa Adel; Zhou, Tao; Xu, Di Ming; Xia, Song; Wen, Yong Zheng; et al. (John Wiley and Sons Inc, 2025)
This study pioneers the cross-disciplinary application of garnet-type solid-state electrolyte Li7La3Zr2O12 (LLZO) in microwave dielectric ceramics. LLZO was synthesized via solid-state reaction, achieving optimized microwave dielectric properties at 900°C: εr = 8.13, Q × f = 31 735 GHz, τf = −44.3 ppm/°C. Direct cofiring experiments with Ag electrodes validated its compatibility with low-temperature cofired ceramic (LTCC). X-ray diffractometer (XRD)/scanning electron microscope (SEM)–energy-dispersive X-ray spectroscopy (EDS) confirmed interfacial stability and chemical inertness, overriding standalone thermal expansion parameter considerations. A Beidou antenna prototype on LLZO substrates demonstrated 59.2 MHz bandwidth at 1.57 GHz with 4.33 dBi gain and >97% radiation efficiency. By synergizing low-loss microwave response with inherent Li⁺ conductivity and thermal robustness, LLZO emerges as a multifunctional platform for integrated energy-communication systems. It enables future designs of LTCC based self-powered modules and real-time structural health monitoring devices. This work bridges solid-state electrolytes and microwave ceramics, offering a paradigm for material innovation in fifth-generation (5G)/sixth-generation (6G) networks and intelligent electronics.